PENGGUNAAN METODE EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VI PADA MATERI MENGIDENTIFIKASI SIFAT-SIFAT MAGNET - Roswana, Wawan (Wahana Pendidikan, 2021)
This study aims to improve students' science learning outcomes on the concept of identifying magnetic properties in class VI SDN 3 Cibunigeulis, Bungursari Tasikmalaya in the 2019/2020 school year. The method used in this research is the classroom action research method. This research was carried out in two cycles by applying the experimental learning method. The stages of this research consist of planning, implementation, observation, and reflection stages. This research was conducted from October to December 2019. The object of this research is 32 students. The results showed that the initial condition before the implementation of the action was the average score of 52.50 students with the proportion of completeness of 12.50%. In the first cycle the average value of the class is 72.97 with a percentage of completeness of 62.50%. In the second cycle the average value of the class is 84.38 with a percentage of completeness of 93.75%. In the second cycle, complete learning has been achieved with a KKM score of 75. The teacher's activities in the first cycle are categorized as good, with a percentage of 70.91%. In the second cycle the percentage increased to 92.73% with a very good category. The activity of students increased from the moderate category in the first cycle with a percentage of 67.5% increased to the very good category with a percentage of 92.5% in the second cycle. Based on the results of these studies, it can be said that the application of the experimental method can improve students' science learning outcomes.Penelitian ini bertujuan untuk meningkatkan hasil belajar IPA peserta didik pada konsep mengidentifikasi sifat-sifat magnet di kelas VI SDN 3 Cibunigeulis Kecamatan Bungursari Kota Tasikmalaya tahun pelajaran 2019/2020. Metode yang digunakan dalam penelitian ini adalah metode penelitian tindakan kelas. Penelitian ini dilaksanakan sebanyak dua siklus dengan menerapkan metode pembelajaran eksperimen. Tahapan penelitian ini terdiri dari tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Penelitian ini dilaksanakan dari bulan Oktober sampai Desember 2019. Objek penelitian ini peserta didik yang berjumlah 32 orang. Hasil penelitian menunjukkan pada kondisi awal sebelum dilaksanakan tindakan nilai rata-rata peserta didik 52,50 dengan persentase ketuntasan sebesar 12,50%. Pada siklus I nilai rata-rata kelas 72,97 dengan persentase ketuntasan sebesar 62,50%. Pada siklus II nilai rata-rata kelas 84,38 dengan presentase ketuntasan sebesar 93,75%. Pada siklus II ini ketuntasan belajar telah tercapai dengan nilai KKM 75. Aktifitas guru pada siklus I berkategori baik, dengan persentase 70,91%. Pada siklus II persentasenya meningkat menjadi 92,73% dengan kategori sangat baik. Aktifitas peserta didik meningkat dari kategori cukup pada siklus I dengan persentase 67,5% meningkat menjadi kategori sangat baik dengan persentase 92,5% pada siklus II. Berdasarkan hasil penelitian tersebut dapat disimpulkan bahwa penerapan metode eksperimen dapat meningkatkan hasil belajar IPA peserta didik.